2013
DOI: 10.1021/ja410379x
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Isomerization and Hydrosilylation Catalysis by Lewis Acidic Organofluorophosphonium Salts

Abstract: Organofluorophosphonium salts of the formula [(C6F5)(3-x)Ph(x)PF][B(C6F5)4] (x = 0, 1) exhibit Lewis acidity derived from a low-lying σ* orbital at P opposite F. This acidity is evidenced by the reactions of these salts with olefins, which catalyze the rapid isomerization of 1-hexene to 2-hexene, the cationic polymerization of isobutylene, and the Friedel-Crafts-type dimerization of 1,1-diphenylethylene. In the presence of hydrosilanes, olefins and alkynes undergo efficient hydrosilylation catalysis to the alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(106 citation statements)
references
References 37 publications
5
98
0
3
Order By: Relevance
“…This observation is similar to that reported for the hydrosilylation of methoxy-α-methylstyrenes (23). The carboxylic acid p-C 8 H 17 (C 6 H 4 )CO 2 H and Et 3 SiH gave the corresponding ester in less than 1 h (entry 21).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This observation is similar to that reported for the hydrosilylation of methoxy-α-methylstyrenes (23). The carboxylic acid p-C 8 H 17 (C 6 H 4 )CO 2 H and Et 3 SiH gave the corresponding ester in less than 1 h (entry 21).…”
Section: Resultssupporting
confidence: 88%
“…The species [(C 6 F 5 ) 3 PF][B(C 6 F 5 ) 4 ] 1 proved to be an effective catalyst for the hydrodefluorination of fluoroalkanes in the presence of silane (22). We subsequently showed that 1 could effectively catalyze the hydrosilylation of olefins and alkynes (23). In this report, we first exploit the Lewis acidity of 1 to catalyze the dehydrocoupling of silane with a variety of species including amines, thiols, phenols, and carboxylic acids, liberating H 2 .…”
mentioning
confidence: 99%
“…The fact that tertiary carbocations are more stable than secondary ones (the latter formed in-situ from nonsubstituted dienes) is reflected in the difference of attainable polymerization degrees. Using organofluorophosphonium salts as catalyst in relatively low catalyst loading of 1.5 mol %, Stephan and coworkers reported high yields (above 89%) for the hydrosilylation of various olefins and alkynes [56]. The reactions were performed at r.t. Based on calculation studies, they proposed a mechanism of the hydrosilylation and the phosphonium activation of hydrosilane.…”
Section: Non-metal Catalysts For Hydrosilylation Reactionsmentioning
confidence: 99%
“…Related trans-hydrosilylations have been achieved with organofluorophosphonium salts as Lewis acid. 44 These methods, however, have not yet been used in the context of natural product synthesis.…”
Section: Introductionmentioning
confidence: 99%